Influência do polimorfismo do fator regulador de interferon 4 (rs1877176) na clínica e nos níveis séricos do interferon-gama, em pacientes com anemia falciforme - Nojosa, Antonia Karine Barros (2023)
In sickle cell anemia (SCA), chronic inflammation is associated with endothelial damage, hemolysis products, and generation of reactive oxygen species (ROS). Increased levels of cytokines such as interferon-gamma (IFN-γ) and genetic polymorphisms may interfere with the prognosis of patients with SCA, emphasizing that polymorphisms in interferon-regulating factors (IRF) are associated with inflammation and interferon synthesis. The aim of this study was to evaluate the influence of interferon regulatory factor 4 (IRF4) polymorphism in the rs1877176 region, with clinical complications and with the serum IFN-γ profile in patients with SCA. This is a cross-sectional and analytical study, including 72 patients diagnosed with SCA (HbSS) undergoing treatment at the Hematology and Hemotherapy Center of Ceará (HEMOCE) and 87 blood donors as a control group (HbAA). Sociodemographic (age and gender), laboratory (HbS, HbF, HbA2, complete blood count, reticulocyte count, LDH, indirect bilirubin, AST) and clinical data [time of diagnosis, use of hydroxyurea (HU) and clinical complications: pain crisis, vaso-occlusive crisis, cerebrovascular accident (AVC), acute chest syndrome (STA), osteomyelitis, recurrent infections, renal alterations, heart disease, hepatomegaly, cholelithiasis, splenic sequestration crisis and leg ulcer] were obtained of clinical records. The analysis of the polymorphism was performed by the real-time polymerase chain reaction (PCR) technique using a TaqMan® probe. Serum IFN-γ levels were measured by enzyme-linked immunosorbent assay (ELISA). Statistical analyses were performed using SPSS® version 22 and GraphPad Prism® 6.01 software, adopting p < 0.05. The results of this study showed that most of the patients were female, aged between 18 and 59 years and using UH. Regarding the allelic and genotypic frequency of the IRF4 gene polymorphism in the rs1877176 region, the G allele (mutant) and the GG genotype (mutant homozygote) were more prevalent in patients and controls, with no statistical difference between these groups. The A allele (wild) was found to confer a higher risk of developing stroke. There was no significant difference between the polymorphism and the laboratory parameters. There was a significant increase in serum IFN-γ levels in patients with SCA compared to the control group and the presence of the GG genotype was associated with reduced serum IFN-γ levels. It is concluded that the presence of the G allele and the GG genotype in FA for IRF4 in the rs1877176 region configures protection against clinical complications such as stroke, as well as for the reduction in IFN-γ levels, thus modulating the inflammatory process in the disease.